2022
DOI: 10.2460/javma.21.10.0462
|View full text |Cite
|
Sign up to set email alerts
|

Effect of empirical versus definitive antimicrobial selection on postoperative complications in dogs and cats undergoing total ear canal ablation with lateral bulla osteotomy: 120 cases (2009–2019)

Abstract: OBJECTIVE To evaluate dogs and cats undergoing total ear canal ablation with lateral bulla osteotomy (TECA-LBO), document antimicrobial choices, and determine relationships associated with infection-related and neurologic postoperative complications. ANIMALS 107 client-owned dogs and 13 client-owned cats that underwent TECA-LBO. PROCEDURES A retrospective analysis of medicals records of dogs and cats with TECA-LBO from 2 veterinary hospitals with postoperative data for at least 6 months was performed. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…8,9 In domestic species, there is a significant risk of perioperative morbidity, with complications including facial nerve paresis, hypoglossal nerve dysfunction, Horner's syndrome, vestibular disease, haemorrhage, fistula formation, and infection. 1,2,[10][11][12] As described in this case, transient facial nerve dysfunction secondary to neuropraxia is a common complication, described in 48.9% of cases in one study, 1 and comparable to historic datasets. [10][11][12] Residual deficits of the facial nerve were present in only 10.5% of cases.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…8,9 In domestic species, there is a significant risk of perioperative morbidity, with complications including facial nerve paresis, hypoglossal nerve dysfunction, Horner's syndrome, vestibular disease, haemorrhage, fistula formation, and infection. 1,2,[10][11][12] As described in this case, transient facial nerve dysfunction secondary to neuropraxia is a common complication, described in 48.9% of cases in one study, 1 and comparable to historic datasets. [10][11][12] Residual deficits of the facial nerve were present in only 10.5% of cases.…”
Section: Discussionmentioning
confidence: 74%
“…Total ear canal ablation combined with lateral bulla osteotomy (TECA‐LBO) is a common salvage procedure for end stage otitis media and externa refractory to medical management, and for the surgical management of aural masses in both the cat and dog 1,2 . The technique has also been adapted and described in the alpaca ( Vicugna pacos ), 3 American bison ( Bison bison ), 4 Atlantic harbor seal ( Phocavitulina concolor ), 5 bongo ( Tragelaphus eurycerus ), 6 chinchilla ( Chinchilla lanigera ), 7 and the domestic rabbit ( Oryctolagus cuniculus ) 8,9 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not surprisingly, most studies have identified incisional infections occurring in up to 10.7% of TECABO cases in the short‐ and long‐term postoperative period (Beckman et al., 1990; Guillamumot et al., 2011; Mason et al., 1988; Matthiesen & Scavelli, 1990; Sharp, 1990; Smeak & Dehoff, 1986). A more recent report followed dogs at least 6 months postoperatively and found an incidence of 24.9%; 46.2% of which required revision surgery (Folk et al., 2022).…”
Section: Introductionmentioning
confidence: 99%